Kinerja Dinas Penanaman Modal dan Pelayanan Satu Pintu Kota Bitung (Pengelolaan Sumberdaya Pembangunan, 2021)
The performance of public organizations, especially in Indonesia, is in the spotlight because of the many complaints from service users. Therefore, realizing a good performance of government organizations requires serious efforts from stakeholders. This study aims to analyze the performance of the Investment Service and One Stop Integrated Services of Bitung City as an organization as a whole. This research method uses descriptive qualitative research methods. Primary data obtained from interviews, observation and documentation. The number of informants was taken as many as 10 informants consisting of 4 Heads of Section, 4 general functional (staff) of the Office of Investment and One Stop Services of Bitung City and 2 people who use the services of the Investment Service and One Stop Integrated Service of Bitung City. person. The results of research on the career development of civil servants in the Bitung City Government show that: 1) there has been a decrease in the quantity or number of services from 2017 and 2018. 2) Service quality has experienced several problems such as there are still complaints from people who still do not know about SOPs. 3) The form of accountability is divided into 2 parts, namely internally to superiors and to agencies. 4) The aspect of responsiveness is in the form of carrying out the vision and mission of the institution in accordance with the vision and mission of the mayor of Bitung. Apart from that, the responsiveness of the office is to capture the aspirations of the community through both direct and online complaint media. 5) The form of institutional responsibility is the accountability for performance by individual employees both to superiors and to fellow employees.Keywords: Performance, Organizational Performanc